The Viral of Hadist: Dimensi dan Makna Meme #Hadis Dalam Media Sosial Instagram - Fernando, Henky; Larasati, Yuniar Galuh; Qudsy, Saifuddin Zuhri (Satya Widya: Jurnal Studi Agama, 2023)
The dissemination of hadith meme images through the #hadis hashtag on Instagram social media has brought up complex and contextual dimensions and meanings. The studies that have discussed this context have only focused on aspects of communication, so the dimensions and meanings of hadith meme images disseminated on Instagram social media have not been comprehensively explained. This study focuses on the question "What are the dimensions and meanings of hadith meme images in the hashtag #hadith disseminated on Instagram social media?" To answer this question, this study uses a netnographic method that is descriptive qualitative in investigating the characteristics and meaning behind a hadith meme image disseminated on Instagram social media. The findings in this study show that the dimensions of hadith meme images in the hashtag #hadith disseminated through Instagram social media appear in three dimensions, namely; images of hadith memes with spiritual, cultural, and social dimensions. The three dimensions of the hadith also contain motivational, evaluative, and reflective meanings. This study also recommends the importance of studies that explain the factors for the emergence of these hadith meme images by interviewing Instagram social media users who upload meme images, in order to gain a comprehensive and more empirical understanding.